Dietary Saccharomyces cerevisiae culture replacement to low-fishmeal enhances growth, intestinal health, muscle quality, and Vibrio parahaemolyticus resistance for Litopenaeus vannamei - Qingxia Luo; Mpwaga Alatwinusa Yohana; Jiaron Chai; Huaxing Lin; Jiandong Chen; Honghao Jin; Beiping Tan; Qihui Yang (Animal Feed Science and Technology, 2026)

Novel cembranoid diterpenoids from the leaves of Nicotiana tabacum with anti-proliferative activity - Xin-Yao Li; Jia-Lin Zhang; Ming-Zhen Liu; Qingxia Zheng; Guo-Xu Ma; Zhong-Hao Sun; Hua Wei (Natural Product Research, 2026)

Synergistic electronic-spatial design in hollow multi-shell FeCo@MoS2 nanoreactors for efficient electrochemical CO2-to-CH4 conversion - Nan Wang; Riguo Mei; Zhongwei Chen; Tao Yang; Xidong Lin; Qingxia Liu (Chemical Engineering Journal, 2026)

Deep Learning-Based Monthly Runoff Simulation in Changing Environments: Enhancing Accuracy by Reducing Data Redundancy - Shenghong Liu; Ji Liu; Shaokang Yang; Zhenxin Bao; Shan-e-hyder Soomro; Wenjuan Chang; Qingxia Lin; Qirui Zhang; Gantao Yang; Ruilin Geng; Haiyu Wang; Longteng Dai (Water Resources Management, 2026)

Enhancement of iron-loaded sewage sludge biochar as substrate for Cr removal in vertical flow artificial wetlands: The critical role of iron - Liheng Liu; Jiahao Chen; Qingxia Huang; Jinchao Wang; Xuehong zhang; Hua Lin; Guo Yu (Bioresource Technology, 2026)

A framework for identifying discriminative model, key factors, and precipitation blocking threshold on triggering drought propagation in the Xijiang River Basin (XRB) - Shinan Zhang; Qingxia Lin; Wenjuan Chang; Zhiyong Wu; Tao Peng; Jiali Guo; Xinzhi Wang (Climate Dynamics, 2026)

Assessment of dynamic drought risk and transition characteristics by combining an indicator-based approach and Markov chain model - Bin Huang; Tao Peng; Tianyi Fan; Vijay P. Singh; Xiaohua Dong; Qingxia Lin; Wenjuan Chang; Ji Liu; Yan Huang; Jiali Guo; Yinghai Li; Dan Yu (Natural Hazards, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Coupled surface water-groundwater-crop model considering the impact of irrigation using different calibration targets - Yuliang Zhang; Jiejie Zhang; Vijay P. Singh; Yuliang Zhou; Yi Cui; Qingxia Lin; Juliang Jin; Shaowei Ning; Zhiyong Wu; Rongxing Zhou; Jieru Yan; Shiqin Xu (Journal of Hydrology, 2026)

Body Composition-Derived Subtypes in Tibetan Adults Residing at Qinghai-High Plateau and Their Associations with Distinct Metabolite Profiles and Cardiometabolic Outcomes - Tiemei Li; Lin Shi; Qingxia Huang; Ruijie Xu; Bin Zhang; Dan Zhang; Qi Wang; Haijing Wang; Li Tong; Huiru Tang; Youfa Wang; Wen Peng (Phenomics, 2025)

A carrier-assisted strategy for accelerating aerobic granulation under low superficial gas velocity: Critical contributions of sediment biochar and camellia shell biochar carriers - Qingxia Lin; Chuxuan Song; Jun Li; Ziqiang Liu; Xue Hu; Rui Xue; Suiqin Yang; Yang Gao; Wei Zhang; Lean Zhou; Julong Sun; Jinting Wang; et al. (Environmental Research, 2025)

New insight into intestinal toxicity accelerated by aged microplastics with triclosan: Inflammation regulation by gut microbiota-bile acid axis - Dawu Lin; Xiangyu Chen; Xiaojun Lin; Chaonan Zhang; Taojie Liang; Li Zheng; Yanbin Xu; Lu Huang; Qingxia Qiao; Kairong Xiong (Journal of Hazardous Materials, 2025)

Spatiotemporal response of agricultural drought to meteorological drought in the upper Hanjiang River Basin from three-dimensional perspective - Shenghong Liu; Shaokang Yang; Ji Liu; Te Zhang; Qingxia Lin; Wenjuan Chang; Tao Peng; Dan Yu (Agricultural and Forest Meteorology, 2025)

Uptake of plasmid reduces the adaptation of Shigella flexneri to disinfectants and increases transmission of antibiotic resistance genes - Xiaojun Lin; Ruiqi Han; Huishi Peng; Junwei Huang; Yanbin Xu; Qingxia Qiao; Lu Huang (International Biodeterioration & Biodegradation, 2025)

A Review on Research of Load Reduction and Ballistic Stability During Cross-Media Water Entry Processes - Qingxia Lu; Xiaojian Ma; Jing Zhao; Lin Shen (Journal of Marine Science and Engineering, 2025)
The cross-media water entry problem widely exists in fields such as ocean engineering and aerospace. The highly non-stationary characteristics of the cross-media water entry process significantly influence the structural strength and ballistic stability of vehicles. This paper selects air-dropped torpedoes, supercavitating vehicles, and high-speed projectiles as three typical types of cross-media vehicles for study. Based on their unique structural characteristics and typical water entry conditions, this paper focuses on the current status of their respective impact load and load reduction challenges, as well as water entry ballistic stability issues. At the research methodological level, this paper systematically reviews the progress of current research in three directions: theory, experiments, and numerical simulations, and introduces the application of artificial intelligence in solving cross-media problems. Finally, this paper looks forward to future development trends in cross-media water entry research, aiming to provide a reference for structural optimization design, motion stability control, and other related studies of cross-media vehicles.

PTA environmental provisions and the export of energy-consuming products: evidence from China - Wen Yue; Qingxia Lin (Environment, Development and Sustainability, 2024)

Metabolite profiles of distinct obesity phenotypes integrating impacts of altitude and their association with diet and metabolic disorders in Tibetans - Wen Peng; Lin Shi; Qingxia Huang; Tiemei Li; Wenxiu Jian; Lei Zhao; Ruijie Xu; Tianqi Liu; Bin Zhang; Haijing Wang; Li Tong; Huiru Tang; et al. (Science of The Total Environment, 2024)

Enhanced aerobic granular sludge by thermally-treated dredged sediment in wastewater treatment under low superficial gas velocity - Qingxia Lin; Shiquan Sun; Jianbin Yang; Pei Hu; Zhengrong Liu; Ziqiang Liu; Chuxuan Song; Suiqin Yang; Fangtong Wu; Yang Gao; Wei Zhang; Lean Zhou; et al. (Journal of Environmental Management, 2024)

Triclosan-loaded aged microplastics exacerbate oxidative stress and neurotoxicity in Xenopus tropicalis tadpoles via increased bioaccumulation - Dawu Lin; Zifeng Cen; Chaonan Zhang; Xiaojun Lin; Taojie Liang; Yanbin Xu; Li Zheng; Qingxia Qiao; Lu Huang; Kairong Xiong (Science of The Total Environment, 2024)

Tapping the potential of anammox upgrading in full-scale wastewater treatment plants through biofilm-enhanced anammox and denitrification - Junwei Huang; Gang Wang; Ruizhi Dai; Jinsong Liao; Yuxin Li; Yiguo Hong; Jiapeng Wu; Qingxia Qiao; Jih-Gaw Lin; Yanbin Xu (Journal of Cleaner Production, 2024)

Attribution analysis of non-stationary hydrological drought using the GAMLSS framework and an improved SWAT model - Youxin Wang; Tao Peng; Yanhu He; Vijay P. Singh; Qingxia Lin; Xiaohua Dong; Tianyi Fan; Ji Liu; Jiali Guo; Gaoxu Wang (Journal of Hydrology, 2023)

Homozygous variants in CDC23 cause female infertility characterized by oocyte maturation defects - Huizhen Fan; Zhou Zhou; Wei Zheng; Yichun Guan; Qingxia Meng; Wenjing Wang; Jie Dong; Liuxia Wan; Jiawei Zhu; Yang Zeng; Ruyi Liu; Hao Gu; et al. (Human Genetics, 2023)

Oxidative Stress in Diabetic Peripheral Neuropathy: Pathway and Mechanism-Based Treatment - Qingxia Lin; Kezheng Li; Yinuo Chen; Jiali Xie; Chunxue Wu; Can Cui; Binbin Deng (Molecular Neurobiology, 2023)

DEHP mediates drug resistance by metabolic reprogramming in colorectal cancer cells - Yue Wu; Ruijie Lu; Yujie Lin; Jinjin Wang; Zijian Lou; Xiaochun Zheng; Ling Zhang; Ruolang Pan; Gang Lu; Qingxia Fang (Environmental Science and Pollution Research, 2023)
Long-term exposure to diethylhexyl phthalate (DEHP), an endocrine-disrupting chemical (EDCs) and plasticizer widely used in consumer products, has been reported to be significantly positively correlated with increased risks of different human diseases, including various cancers, while the potential effect of DEHP on colorectal cancer progression was little studied. In the present study, we showed that DEHP could trigger the metabolic reprogramming of colorectal cancer cells, promote cell growth and decrease fluorouracil (5-FU) sensitivity. Mechanistic studies indicated that DEHP could reduce glycolysis activity and increase oxidative phosphorylation (OXPHOS) in SW620 cells. In addition, in vivo experiments showed that DEHP promoted tumorigenic progression and decreased survival time in mice. Collectively, our findings suggest that DEHP may be a potent risk factor for colorectal cancer development.

Propagation from meteorological to hydrological drought and its application to drought prediction in the Xijiang River basin, South China - Qingxia Lin; Zhiyong Wu; Yuliang Zhang; Tao Peng; Wenjuan Chang; Jiali Guo (Journal of Hydrology, 2023)

Hydrological drought dynamics and its teleconnections with large-scale climate indices in the Xijiang River basin, South China - Qingxia Lin; Zhiyong Wu; Jingjing Liu; Vijay P. Singh; Zheng Zuo (Theoretical and Applied Climatology, 2022)

Sex differences in microstructural alterations in the corpus callosum tracts in drug-naïve children with ADHD - Qingxia Lin; Xuan Bu; Hong Chen; Yan Liang; Weiqian Wang; Yanhong Yi; Haixi Lin; Lu Lu; Yingxue Gao; Andan Qian; Shuangli Chen; Meihao Wang; et al. (Brain Imaging and Behavior, 2022)

A New Non-stationary Hydrological Drought Index Encompassing Climate Indices and Modified Reservoir Index as Covariates - Youxin Wang; Tao Peng; Qingxia Lin; Vijay P. Singh; Xiaohua Dong; Chen Chen; Ji Liu; Wenjuan Chang; Gaoxu Wang (Water Resources Management, 2022)

Different effects of the DRD4 genotype on intrinsic brain network connectivity strength in drug-naïve children with ADHD and healthy controls - Shuangli Chen; Andan Qian; Jiejie Tao; Ronghui Zhou; Chuqi Fu; Chuang Yang; Qingxia Lin; JieJie Zhou; Jiance Li; Xiaoqi Huang; Meihao Wang (Brain Imaging and Behavior, 2022)
The dopamine D4 receptor gene (DRD4) has been consistently reported to be associated with attention-deficit/hyperactivity disorder (ADHD). Recent studies have linked DRD4 to functional connectivity among specific brain regions. The current study aimed to compare the effects of the DRD4 genotype on functional integrity in drug-naïve ADHD children and healthy children. Resting-state functional MRI images were acquired from 49 children with ADHD and 37 healthy controls (HCs). We investigated the effects of the 2-repeat allele of DRD4 on brain network connectivity in both groups using a parameter called the degree of centrality (DC), which indexes local functional relationships across the entire brain connectome. A voxel-wise two-way ANCOVA was performed to examine the diagnosis-by-genotype interactions on DC maps. Significant diagnosis-by-genotype interactions with DC were found in the temporal lobe, including the left inferior temporal gyrus (ITG) and bilateral middle temporal gyrus (MTG) (GRF corrected at voxel level p < 0.001 and cluster level p < 0.05, two-tailed). With the further subdivision of the DC network according to anatomical distance, additional brain regions with significant interactions were found in the long-range DC network, including the left superior parietal gyrus (SPG) and right middle frontal gyrus (MFG). The post-hoc pairwise analysis found that altered network centrality related to DRD4 differed according to diagnostic status (p < 0.05). This genetic imaging study suggests that the DRD4 genotype regulates the functional integration of brain networks in children with ADHD and HCs differently. This may have important implications for our understanding of the role of DRD4 in altering functional connectivity in ADHD subjects.

Aberrant white matter properties of the callosal tracts implicated in girls with attention-deficit/hyperactivity disorder - Qingxia Lin; Xuan Bu; Meihao Wang; Yan Liang; Hong Chen; Weiqian Wang; Yanhong Yi; Haixi Lin; Jiaxiu Zhou; Lu Lu; Xinyu Hu; Chuang Yang; et al. (Brain Imaging and Behavior, 2020)

Tetramethylpyrazine Promotes Migration of Neural Precursor Cells via Activating the Phosphatidylinositol 3-Kinase Pathway - Xiangying Kong; Micun Zhong; Xiaohui Su; Qingxia Qin; Hongchang Su; Hongye Wan; Cuiling Liu; Jiajia Wu; Hongcai Shang; Yanjun Zhang; Na Lin (Molecular Neurobiology, 2016)

Exploring spatiotemporal relationships among meteorological, agricultural, and hydrological droughts in Southwest China - Zhiyong Wu; Yun Mao; Xiaoyan Li; Guihua Lu; Qingxia Lin; Huating Xu (Stochastic Environmental Research and Risk Assessment, 2016)

Development of a Large-Scale Routing Model with Scale Independent by Considering the Damping Effect of Sub-Basins - Guihua Lu; Jingjing Liu; Zhiyong Wu; Hai He; Huating Xu; Qingxia Lin (Water Resources Management, 2015)

Analysis of hydrological drought frequency for the Xijiang River Basin in South China using observed streamflow data - Zhiyong Wu; Qingxia Lin; Guihua Lu; Hai He; John J. Qu (Natural Hazards, 2015)

Discordant genotypic resistance and HIV-1 genetic diversity from paired plasma and cerebrospinal fluid samples in Chinese settings - Lifeng Liu; Yulin Zhang; Feili Wei; Qingxia Zhao; Xicheng Wang; Lin Yuan; Ning Li; Dexi Chen (Journal of NeuroVirology, 2013)

SNP identification and allelic-specific PCR markers development for TaGW2, a gene linked to wheat kernel weight - Zibo Yang; Zhiyuan Bai; Xiaolin Li; Pei Wang; Qingxia Wu; Lin Yang; Liqun Li; Xuejun Li (Theoretical and Applied Genetics, 2012)

Identification of the VP92R gene from infectious spleen and kidney necrosis virus - Xiaopeng Xu; Qingxia Lu; Rui Wang; Ting Lin; Shaoping Weng; Ling Lu; Zhongsheng Li; Xiaoqiang Yu; Junliang Tang; Jianguo He (Virus Genes, 2010)

Effects of CYP2C19 and CYP2C9 genotypes on pharmacokinetic variability of valproic acid in Chinese epileptic patients: nonlinear mixed-effect modeling - Dechun Jiang; Xiangrong Bai; Qingxia Zhang; Wei Lu; Yuqin Wang; Lin Li; Markus Müller (European Journal of Clinical Pharmacology, 2009)